2008
DOI: 10.1080/00131880802499803
|View full text |Cite
|
Sign up to set email alerts
|

The impact of teacher factors on achievement and behavioural outcomes of children with Attention Deficit/Hyperactivity Disorder (ADHD): a review of the literature

Abstract: Background: Attention Deficit/Hyperactivity Disorder (ADHD) is a common disorder known to be associated with behavioural and academic difficulties. Several treatment options are available for children with ADHD, such as medication and behavioural therapy. Although researchers have examined the efficacy of these approaches, much less is understood about how teacher factors, including attitudes and beliefs about ADHD and treatment options, can influence students' behavioural and learning outcomes. Purpose: The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 30 publications
2
66
0
8
Order By: Relevance
“…Perceptions of ADHD have also been found to be related to treatment acceptability (Graczyk, et al, 2005: Vereb & DiPerna, 2004) and self-confidence (Graczyk, et al, 2005;Sciutto et al, 2000). In reviews of the literature on teacher factors, perceptions of ADHD have been cited as important variables in need of future research for better understanding how to improve interventions and trainings with teachers (Sherman et al, 2008;Kos et al, 2006;Glass & Wegar, 2000). Operationalized definitions of teacher expectations still need to be constructed and tested for predictive utility.…”
Section: Chapter IV Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions of ADHD have also been found to be related to treatment acceptability (Graczyk, et al, 2005: Vereb & DiPerna, 2004) and self-confidence (Graczyk, et al, 2005;Sciutto et al, 2000). In reviews of the literature on teacher factors, perceptions of ADHD have been cited as important variables in need of future research for better understanding how to improve interventions and trainings with teachers (Sherman et al, 2008;Kos et al, 2006;Glass & Wegar, 2000). Operationalized definitions of teacher expectations still need to be constructed and tested for predictive utility.…”
Section: Chapter IV Discussionmentioning
confidence: 99%
“…It is likely that teachers' perceptions of students with ADHD affect their behavior with students (Glass & Wegar, 2000;Kos et al, 2006). Teacher factors such as tolerance of classroom behaviors, level of training, and treatment acceptability have been shown to affect learning and social outcomes for students with ADHD (Sherman, Rasmussen, & Baydala, 2008).…”
mentioning
confidence: 99%
“…Their support is needed for the results of the treatment received by the student to be successful, and their views and opinions about ADHD have a profound effect on the treatment's efficacy (Sherman, Rasmussen & Baydala, 2008). In this context it has been demonstrated that teachers' knowledge of effective treatment for ADHD has an effect on the support they provide for those treatments (Ohan et al, 2008).…”
Section: Adhd and Teachersmentioning
confidence: 99%
“…According to Sherman et al (2008), the relevant variables that distinguish the teacher specially trained to assist and support students with ADHD are patience, knowledge of effective intervention techniques, the ability to collaborate with a multidisciplinary team, the use of gestures to communicate with students and a positive attitude towards children with special educational needs. In the same vein authors such as Pfiffner (1999) and Cooper and Bilton (2002) highlight two teacher factors that are key to the success of students with ADHD: knowledge and education about the disorder, and a positive attitude towards and perception of the recommended psychological and educational interventions.…”
Section: Adhd and Teachersmentioning
confidence: 99%
“…1,2 It is characterized by a suite of symptoms that include inattention, increased motor activity, and a tendency to show an aggressive behavior or impulsivity [3][4][5] and affected individuals often show poorly adjusted social behavior. 6 The diagnostic and statistical manual of mental disorders (DSM-5) distinguishes three presentations of ADHD depending on the predominant symptom pattern for the past six months 7 : combined presentation (presence of the core features hyperactivity/impulsivity and inattention; presence of ≥6 symptoms/feature), predominantly inattentive presentation (≥6 symptoms of inattention, ≤6 symptoms of hyperactivity/impulsivity) and predominantly hyperactive/impulsive presentation (≥6 symptoms of hyperactivity/ impulsivity, ≤6 symptoms of inattention).…”
Section: Introductionmentioning
confidence: 99%